2017
DOI: 10.1515/pepsi-2017-0003
|View full text |Cite
|
Sign up to set email alerts
|

Religious Identity Status and Readiness for Interreligious Dialogue in Youth. Developmental Analysis

Abstract: The aim of the article is to show statuses of religious identity in Polish Catholic adolescents. The distinguished statuses result from intensive consolidation processes which are characteristic of this age. Integration of religious identity has an effect on potential openness versus reluctance to interreligious dialogue. The study was conducted on 60 participants at the ages of 18 to 29 using the Scale of Religious Identity by Wieradzka-Pilarczyk (2015) and Centrality of Religiosity Scale Z-15 by S. Huber (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 12 publications
1
2
0
Order By: Relevance
“…Relativism and external critique, which are the measures of the religious attitudes in a secularized context, correlated negatively with centrality (Bartczuk et al 2011). These results are supported by Rydz and Wieradzka-Pilarczyk (2018) research, which showed that people with internalized religious identity status had higher scores in centrality, whereas people seeking religious identity status had lower scores in centrality. The research on emotions and attachment to God further broadened these findings.…”
Section: A Review Of the Reserch Involving Polish Crssupporting
confidence: 61%
“…Relativism and external critique, which are the measures of the religious attitudes in a secularized context, correlated negatively with centrality (Bartczuk et al 2011). These results are supported by Rydz and Wieradzka-Pilarczyk (2018) research, which showed that people with internalized religious identity status had higher scores in centrality, whereas people seeking religious identity status had lower scores in centrality. The research on emotions and attachment to God further broadened these findings.…”
Section: A Review Of the Reserch Involving Polish Crssupporting
confidence: 61%
“…Later, a dimension of ruminative exploration has been added to the model (Luyckx et al 2008). Rydz and Wieradzka-Pilarczyk (2017) developed the scale measuring the dimensions of this model in the religious domain.…”
Section: Religion Religious Identity and Religious Identity Statusmentioning
confidence: 99%
“…As a result, intergroup contact is regarded as one of the most effective means of reducing prejudice (Boin et al 2021). Contact between groups to minimize religious prejudice has been widely employed in a variety of social contexts, including education and teaching in schools and universities with the use of terminology, including 'interfaith learning' (Goldberg 2020;Mayhew and Rockenbach 2021), 'inter-religious education' or 'interfaith education' (e.g., Engebretson et al 2010;Wielzen and Avest 2017), and 'inter-faith dialogue' or 'inter-religious dialogue' (Ariarajah 2019;Rydz and Wieradzka-Pilarczyk 2017). The concept behind interfaith learning is that strong interfaith interactions underlie the acquisition of knowledge, attitudes, beliefs, and behaviors for positive relationships among people of different religions or worldviews (Mayhew and Rockenbach 2021;Rockenbach et al 2020;Wielzen and Avest 2017).…”
Section: Introductionmentioning
confidence: 99%